The Degree of Success in Environmental Mitigation Measures of Development Projects in Sri Lanka with Special Reference to Peraru Water Supply and Sanitation Project - Mohammed, Asmi; Weerasinghe , Tamara K. (European Journal of Applied Sciences, 2021)
Human life and element of nature is well connected. Man-made activities can destroy the natural system which sustains the human life. In many parts of the world, economic development projects directed at improving levels of material comfort have had unintended detrimental effects on people and natural resources. Water, land, and air have been degraded to the point where they can no longer sustain existing levels of development and quality of life. Economic development in developing countries has been focused on immediate economic gains environmental protection has not been a priority because the economic losses from environmental degradation often occur long after the economic benefits of development have been realized. Environmental Management Plans (EMP) are used in development projects to mitigate the anticipated impacts due the project intervention. EMP is monitored periodically using performance indicators shown in the Environmental Monitoring Plan (EMoP). As per National Environmental Act, all the mega development activities must have an EMP. Some development projects effectively implement the EMP but there are cases that the implementation is not being practiced as per the EMP. This study assessed how effectively EMP was implemented in Per Aru Water Supply and Sanitation Project. A structured interview guideline was used to collect and obtain information from the target group. The study analysed impact and mitigation on key environmental factors such as air, water, land, fauna and flora. Throughout the study, it was found that the implementation of EMP was successful. Project had planted around 176,972 plants for removing 1600 trees; Followed enough mitigation measures riprap and turfing to control the erosion in the bund; less mobile species were translocated to similar habitat area; no degradation occurred to the water body surrounding the project area; however project had failed to take enough mitigation measures on dust, translocating the flora and releasing the environmental flow. It is recommended to release the environmental flow, form a grievance redress mechanism to solve environmental related peoples’ complains and grievances, improve the community consultation, increase the project approving agencies monitoring on the implementation of EMP, and control the invasive plants Muntingia calabura (Jam fruit tree). Further, recommended to donor agencies to evaluate the successfulness of the implemented EMP after project completion